An observational study on the prevalence of hearing loss among construction workers in South Chennai - Ram Prabu O G; Namasivaya Navin R B; Prabakaran S; Muthukumar R; Rajasekaran S; Balaji D; Gowthame K; Sarath Kumar B (International Journal of Occupational Safety and Health, 2025)
Introduction: The construction industry is one of the biggest industries in the world. Noise levels are considered hazardous when they reach 85 decibels or higher. Hearing loss adversely affects both the quality of life and the risk of damage. The study's primary objective was to estimate the prevalence of hearing loss among construction workers, and the secondary objective was to assess the factors associated with hearing loss among construction workers in the urban area of Chennai.